XMM-Newton (X-Ray Mulit-Mirror Mission) Observatory - Lumb, David H; Schartel, Norbert; Jansen, Fred A (arXiv.org, 2012)
X-ray Multi-Mirror Mission (XMM-Newton) has been one of the most successful astronomy missions launched by the European Space Agency. It exploits innovative use of replication technology for the X-ray reflecting telescopes that has resulted in an unprecedented combination of effective area and resolution. Three telescopes are equipped with imaging cameras and spectrometers that operate simultaneously, together with a coaligned optical telescope. The key features of the payload are described, and the in-orbit performance and scientific achievements are summarised. Subject terms or keywords: XMM-Newton, X-ray astronomy, space telescopes